A general seed-mediated approach to the synthesis of AgM (M = Au, Pt, and Pd) core–shell nanoplates and their SERS properties. Issue 44 (23rd May 2017) - Kumar-Krishnan, Siva; Estevez-González, M.; Pérez, Ramiro; Esparza, Rodrigo; Meyyappan, M.
Abstract : Graphical abstract describing a general pH-dependent synthetic steps for the preparation of AgM (Au, Pt and Pd) triangular core–shell nanoplates and hollow nanoframes. Abstract : Ag-based bimetallic core–shell nanoplates have received much attention in catalysis, surface-enhanced Raman scattering (SERS), and sensing applications. However, control over the synthesis of core–shell nanostructures still remains a challenge. Herein, we present a facile, seed-mediated synthesis of bimetallic or multimetallic AgM (M = Au, Pt, and Pd) core–shell nanoplates using pre-synthesized triangular Ag nanoplates as seeds in the presence of ascorbic acid, NaOH, and poly(vinylpyrrolidone) at room-temperature. Higher pH was found to be crucial in effectively controlling the galvanic reaction that resulted in a uniform deposition of the shell on the Ag nanoplate seeds. In contrast, synthesizing in a lower pH condition led to the removal of the Ag core via galvanic reaction generating triangular hollow nanoframes comprising of bimetallic AgM (M = Au, Pt, Pd) with well-defined interior gaps. The resultant nanostructures were studied for the SERS performance in the solution-phase using an excitation wavelength of 785 nm. Owing to the tunable plasmonic peaks close to near infrared region of the Ag@Au core–shell nanoplates, greatly enhanced SERS signal was obtained compared to the original Ag nanoplates, Ag@Pt, Ag@Pd, and Ag@PtPd nanostructures. Our approach demonstrates control over the galvanic exchange reaction and thereby makes it possible to synthesize intricate architectures on the nanoscale, opening up promising opportunities for rational designing of multifunctional nanostructures for plasmonics and sensing applications.